1999
DOI: 10.1038/21690
|View full text |Cite
|
Sign up to set email alerts
|

The tyrosine kinase c-Abl regulates p73 in apoptotic response to cisplatin-induced DNA damage

Abstract: Cancer chemotherapeutic agents such as cisplatin exert their cytotoxic effect by inducing DNA damage and activating programmed cell death (apoptosis). The tumour-suppressor protein p53 is an important activator of apoptosis. Although p53-deficient cancer cells are less responsive to chemotherapy, their resistance is not complete, which suggests that other apoptotic pathways may exist. A p53-related gene, p73, which encodes several proteins as a result of alternative splicing, can also induce apoptosis. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
739
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 856 publications
(787 citation statements)
references
References 18 publications
38
739
4
Order By: Relevance
“…8,[20][21] The original, common notion that p73 is not upregulated in response to DNA damage was then challenged by several reports that clearly demonstrated that p73 is a target for c-abl tyrosine kinase in response to DNA damages caused by cisplatin and g-radiation. [22][23][24] Flores et al then observed that the p632/2; p732/2 double null mouse embryo fibroblasts (MEF) were as resistant to apoptosis as p532/2 MEF cells, pointing out that p63 and p73 are required for p53-induced apoptosis and delineating functional interplay between p53 family members. 25 More recent studies have shown that p73 could be implicated in the cellular response to drugs in cancer cells such as squamous cell carcinomas or osteosarcoma cell lines.…”
mentioning
confidence: 99%
“…8,[20][21] The original, common notion that p73 is not upregulated in response to DNA damage was then challenged by several reports that clearly demonstrated that p73 is a target for c-abl tyrosine kinase in response to DNA damages caused by cisplatin and g-radiation. [22][23][24] Flores et al then observed that the p632/2; p732/2 double null mouse embryo fibroblasts (MEF) were as resistant to apoptosis as p532/2 MEF cells, pointing out that p63 and p73 are required for p53-induced apoptosis and delineating functional interplay between p53 family members. 25 More recent studies have shown that p73 could be implicated in the cellular response to drugs in cancer cells such as squamous cell carcinomas or osteosarcoma cell lines.…”
mentioning
confidence: 99%
“…When p73 was identified, it was reported that p73 is not induced by DNA damage, 11 but later on it was found that p73 is indeed induced by a wide variety of DNA-damage-inducing drugs like adriamycin, etoposide, cisplatin, etc. [13][14][15][16][17][18] A recent study has also linked chemosensitivity of cancer cells to functional p73 irrespective of p53 status. 18 It was shown that specific abrogation of p73 leads to chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Although, initially it was reported that p73 is not induced by DNA damage, subsequent studies reported that p73 is indeed induced by a wide variety of DNA-damage-inducing drugs like adriamycin, etoposide, cisplatin, etc. 11,[13][14][15][16][17][18] It was also reported that both p73 and p63 (another p53 family member) play a crucial role in DNA-damage-induced p53-mediated apoptosis. 19 It was shown that combined loss of p63 and p73 results in failure of cells containing wild-type p53 to undergo apoptosis in response to DNA damage.…”
mentioning
confidence: 97%
“…Alternatively, however, it is possible that a second proline-rich domain within p73b eliminates the need for residues 81 ± 113. Accordingly, a proline-rich region within the Cterminal portion of p73 was shown to interact with the c-abl kinase, leading to phosphorylation of p73 and activation of its pro-apoptotic function (Agami et al, 1999;Gong et al, 1999;Yuan et al, 1999). In contrast, no such C-terminal proline-rich domain is found in p53, and the reported interactions of p53 with c-abl (Sionov et al, 1999) were thus proposed to be of a more indirect nature (White and Prives, 1999).…”
Section: Discussionmentioning
confidence: 99%